Pengembangan Pendidikan Agama Islam dalam Menentukan Arah dan Tujuan Sistem Pendidikan Islam di Indonesia: Tinjauan Pemikiran Imam Syafi’i: The Development of Islamic Education in Shaping the Direction and Objectives of the Islamic Education System in Indonesia: A Review of Imam Shafi'i's Thought - Baruza, Barlinty Isbaaniyaa; Silahuddin, Silahuddin; Zulfatmi, Zulfatmi (Published by Center for Research and Community Service (LP2M) in cooperation with the Postgraduate Program of UIN Ar-Raniry Banda Aceh, Aceh, Indonesia., 2024)
Islamic education, by its nature, is an institution that encompasses Islamic teachings. The presence of Islam in the Indonesian archipelago has led to the establishment of educational institutions, both formal and non-formal, which have developed the Shafi'i school of thought within social, cultural, and various other contexts. This study aims to describe the development of Islamic education in Indonesia, focusing on the direction and objectives of Islamic education as viewed through the perspective of Imam Shafi'i, the founder of the Shafi'i school. The methodology employed in this research is a library study. The findings indicate that the Shafi'i school is the most widely accepted school of jurisprudence among Muslims globally, particularly in Indonesia. The presence of the Shafi'i school aligns with the spread of Islam in Indonesia. The development of Islamic education in Indonesia relies significantly on the Shafi'i school as a primary reference for daily religious practices. Educational institutions, whether formal or non-formal, remain closely tied to the teachings of the Shafi'i school. Abstrak Pendidikan Islam pada hakikatnya merupakan lembaga yang di dalamnya terdapat ajaran-ajaran Islam. Kehadiran Agama Islam di Nusantara telah melahirkan lembaga-lembaga Pendidikan di Indonesia, yakni lembaga formal dan lembaga non formal yang telah mengembangkan mazhab Syafi'i dalam konteks social, budaya serta berbagai kebutuhan lainnya. Penelitian ini bertujuan untuk mendeskripsikan tentang pengembangan pendidikan Agama Islam dalam menentukan arah dan tujuan pendidikan Islam di Indonesia yang ditinjau dari pemikiran Imam Mazhab Syafi'i yakni Imam Asy-Syafi’i. Metode yang digunakan dalam penelitian ini yaitu studi kepustakaan. Hasil penelitian mengatakan bahwa mazhab Syafi'i merupakan mazhab fiqih yang paling banyak diterima di kalangan umat Islam di penjuru dunia, terutama di Indonesia. Keberadaan Mazhab Syafi'i sejalan dengan penyebaran Islam di Indonesia. Pengembangan Pendidikan Agama Islam di Indonesia menjadikan paham mazhab Syafi’i ini sebagai salah satu sandaran utama dalam melakukan ibadah di kehidupan sehari-hari. Pada lembaga pendidikan baik di lembaga formal ataupun lembaga non formal tetap tidak jauh dari ajaran yang berpaham dengan mazhab Syafi’i.